ESTIMATION OF RNA/DNA RATIO IN TWO NORTH-INDIAN NATURAL POPULATIONS OF MAHSEER (TOR TOR), AND ITS RELATIONSHIP WITH GROWTH AND HYROBIOLOGY - Mourya, T. C.; Krishna, Gopal; Chaudhari, Aparna (Journal of Indian Fisheries Association, 2007)
Samples of Tor tor were collected from Bari Reservoir of Udaipur and Narmada River at Hoshangabad (India), in the months of July and November 2005, respectively. Twenty-five samples were collected from each location. Bari Reservoir samples ranged from 17.0 to 24.5 em in total length and from 75 to 155 g in weight, while Narmada samples ranged from 20.0 to 42.0 em in length and 90 to 425 g in weight. The nucleic acid content in body muscle of Tor tor and the RNA/DNA ratio were estimated. The age of fishes was estimated by the scale study method and specimens were classified into four age groups. RNA/DNA ratio showed significant linear increase with increase in weight and age till the age of three years after which, the growth rate reduced. The 1-2 year group was the only one common between the two water bodies and a comparison of RNA/DNA ratios showed higher growth rate in Bari Reservoir. The gross primary productivity was also higher in Bari Reservoir being 551 mg cm-3 d-1 compared to 404 mg cm-3 d-1 observed for Narmada River. The condition factor (K) was found to be higher (1.21) in the fish from the Bari Reservoir compared to those of Narmada River (1.14). The growth rate was higher in females compared to males in> 100 g specimens. Keywords: Tor tor, growth, RNA/DNA ratio, condition factor (K)